(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the physical condition of male soccer athletes of the East Java 100-IV training center in preparation for the 2028 PON in NTT-NTB. This study uses non-experimental quantitative descriptive research. The subjects of this study were 25 people. The research instrument uses secondary data from physical tests (test retest) obtained from the results of physical condition tests of East Java Puslatda soccer athletes managed by KONI East Java. The data analysis steps used include various physical test items, including: Sit Up, Single Leg Squat, Russian Twist, Chin Up, Superman Back Hold, Medicinal Ball Throw, Dips, 20-meter Sprint, Illinois Agility Test, Vertical Jump, Triple Jump, Ankle Flexibility (right and left), Sit and Reach, and VO₂max through the Multi-Stage Fitness Test (Bleep Test). The results showed that several components of physical condition such as abdominal muscle strength (Sit Up) and agility (Illinois) were in the good to very good category. However, most of the other components such as leg muscle strength (Single Leg Squat), upper body strength (Chin Up and Dips), ankle flexibility, and cardiovascular endurance (VO₂max) are still considered adequate to lacking. These findings suggest that training programs need to be focused on improving aspects of physical condition that are still weak.